Blood urea nitrogen level in patients with chronic total occlusion predicts long-term mortality independent of estimated glomerular filtration rate and serum creatine level: (9-year follow-up results) - Ozyildiz, Ali Gokhan; Cetin, Mustafa; Ozer, Savas; Duman, Hakan; Kiris, Tuncay (Annals of Medical Research, 2021)
Aim: Increased serum blood urea nitrogen (BUN) level is an indicator of neurohormonal and renal dysfunction, and is associated with the major adverse cardiovascular events (MACE). Chronic total occlusion (CTO) is a typical coronary artery disease diagnosed by coronary angiography. We established and tested the hypothesis that there might be a relationship between serum BUN level and long-term prognosis in patients with CTO. Materials and Methods: The study consisted of 124 patients diagnosed with CTO. The patients were followed up for a mean of 9.2 (7.4-9.5) years, and all-cause mortality was determined. Results: Patients were divided into two groups according to mortality outcome. During the follow-up, 38 of 124 patients died. Univariate Cox analysis showed that age (p=0.002), BUN (p=0.001), and serum creatinine levels (p=0.039) were associated with mortality. BUN level (OR: 1.074; 95% CI: 1.018-1.134; p=0.009) and age (OR: 1.043; 95% CI: 1.001-1.087, p=0.043) were independently associated with mortality in multivariate Cox analysis. In the ROC analysis, the AUC values for BUN and estimated glomerular filtration rate were 0.689 (p=0.002) and 0.650 (p=0.001), respectively. When the cutoff value for BUN level was considered >16 mg/dL, the sensitivity was 68%, and the specificity was 53% (OR:1.38) to predict mortality. When the cutoff value was considered >20 mg/dL, the sensitivity diminished to 40%, while the specificity increased to 90% (OR:3.9). Conclusion: In patients with CTO, BUN level is associated with increased all-cause mortality during long-term following. This relationship is independent of renal dysfunction.